Effect of Invasive Pest Phenacoccus manihoti Matile-Ferrero (Hemiptera; Pseudococcidae) in Cassava - Wardani, Nila; Rauf, Aunu; Winasa, I Wayan; Santoso, Sugeng (International Journal of Environment, Agriculture and Biotechnology, 2019)
Heavy damage by the cassava mealybug, Phenacoccua manihoti Matile-Ferrero (Hempiptera: Pseudococcidae) caused symptoms of bunchy top, shortened and distorted nodes, leaf drops, and inhibition of plant growth. The consequences of these pests can cause yield losses of 80%. This study was to determine the development of P. manihoti and cassava yield loss. Field observations indicated that symptoms of bunchy top appeared as early as 8 weeks after planting (wap) and rose quickly started 16 wap, at the same time with the advent of the dry season (May-June). Level of infestation developed faster on variety Jimbul; at 18 wap all plants had bunchy tops. While on varieties Roti and Manggu, 100% infestation occurred at 30 and 36 wap, respectively. There was a correlation between early infetation with plant height ang yield. Cassava plants infested during early stage were shorter and the yield lower, compared to those infested at further stages. Lower yields of variety Jimbul (0.94 kg/tree) than variety Manggu (3.16 kg/plant), was thought to be related to heavy infestation which occurred during early stage.